2019
DOI: 10.1093/bjsw/bcz133
|View full text |Cite
|
Sign up to set email alerts
|

What Do Service Users Want from Mental Health Social Work? A Best–Worst Scaling Analysis

Abstract: Despite being a profession dedicated to the empowerment of service users, empirical study of mental health social work appears dominated by the perspectives of social workers themselves. What service users value is less often reported. This study, authored by a mix of academics and service users/carers, reports a Best–Worst Scaling analysis of ten social worker ‘qualities’, representing both those highly specialist to social work and those generic to other mental health professionals. Fieldwork was undertaken … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 30 publications
(33 reference statements)
0
7
0
1
Order By: Relevance
“…The larger study was designed to explore the contribution of the social work role in CMHTs for working age adults and older people (Challis et al, 2014). It examined the responsibilities, roles and tasks of social workers in CMHTs through a national survey (reported on here) as well as focus groups with team members (Abendstern et al, 2020); the characteristics of people supported by social workers in CMHTs via a caseload audit; and aspects of CMHT social work practice most valued by service users through faceto-face interviews using a Best-Worst Scaling tool (Wilberforce et al, 2019). Finally, service user and staff experiences were captured via postal surveys.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The larger study was designed to explore the contribution of the social work role in CMHTs for working age adults and older people (Challis et al, 2014). It examined the responsibilities, roles and tasks of social workers in CMHTs through a national survey (reported on here) as well as focus groups with team members (Abendstern et al, 2020); the characteristics of people supported by social workers in CMHTs via a caseload audit; and aspects of CMHT social work practice most valued by service users through faceto-face interviews using a Best-Worst Scaling tool (Wilberforce et al, 2019). Finally, service user and staff experiences were captured via postal surveys.…”
Section: Methodsmentioning
confidence: 99%
“…Within multidisciplinary teams they have been reported to support their non-social work colleagues to ensure the delivery of support that places the service user and their social and familial networks at the heart of practice, providing non-judgemental, strengthsbased input that promotes self-determination and long-term recovery (Abendstern et al, 2014(Abendstern et al, , 2020Allen, 2014;All-Party Parliamentary Group on Social Work, 2016). Evidence from service users and carers suggests that they value social workers for their ability to see them 'in the round', to work in partnership with them, and to provide clear communication (Allen, 2014;Kam, 2019;Vicary & Bailey, 2018;Wilberforce et al, 2019). Service users have reported that social workers, when compared with their health colleagues, deliver more personcentred support (Boland et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This qualitative paper forms part of a larger-mixed methods study that aimed to identify the social work contribution to CMHTs drawing on the characteristics, opinions and experiences of managers, practitioners and service users (Boland et al., 2019; Wilberforce et al., 2019). The views of social workers and their team colleagues were collected via focus groups and analysed using Braun and Clarke’s organic thematic analysis method (2016).…”
Section: Methodsmentioning
confidence: 99%
“…Third, the service-user voice is also absent from this study despite the question posed aiming to understand their experiences. Other elements of the larger study of which this paper forms a part have addressed service users directly, examining their preferences with findings supporting those reported above, particularly in relation to the social workers’ holistic perspective (Wilberforce et al., 2019). Future studies might also consider the implications of the social work role on carers as well as service users.…”
Section: Study Limitationsmentioning
confidence: 97%
“…The involvement of experts by experience in the provision of services challenges social work professionals to revise their views as well as expert organizations to give room to experts by experience in the service system. While social work is dedicated to empowering service users, the social workers' perspective still dominates the setting (Wilberforce et al, 2020). Therefore, teamwork between experts by experience and social workers requires a new kind of mind-set and the sharing of expertise.…”
Section: Introductionmentioning
confidence: 99%